Levantamento do gênero Butia (Becc.) Becc. (Arecaceae) no Rio Grande do Sul - Deble, Leonardo Paz; Marchiori, José Newton Cardoso; Alves, Fabiano da Silva; Oliveira-Deble, Anabela Silveira de (Balduinia, 2014)
Ten species of Butia (Becc.) Becc. were recognized to Rio Grande do Sul State flora: Butia catarinensis, B. eriospatha, B. exilata, B. lallemantii, B. missionera, B. odorata, B. paraguayensis, B. pulposa, B. witeckii and B. yatay. Two new species were presently described: Butia exilata and B. missionera. The natural occurrence of Butia paraguayensis is confirmed to the State flora, being defined its extent of occurrence area. Butia microspadix is excluded to Rio Grande do Sul State flora. Butia stolonifera is defined species dubia. A key to the identification of native species is given, as well as illustrations (photos and drawns).